Comparative Studies of Blood Coagulation in Hibernating and Non-Hibernating Frogs (Rana tigrina) - Ahmad, Nasreen; Dube, B; Agarwal, G P; Dube, Rama Kanta (Thrombosis and Haemostasis, 1979)
1. During hibernation in frogs (Rana tigrina) there occurs prolongation of several clotting tests, viz, whole blood clotting time, plasma recalcification time, cephalin time and prothrombin time.2. The ambient body temperature of the frog during winter hibernation is low and the retarded blood clotting at lower temperature may play an important protective role against intravascular thrombosis.3. Shorter plasma recalcification time in low-spun plasma as compared to high-spun plasma indicated the presence of procoagulant activity in platelets/leucocytes of frogs.